Optimal quality ultra high video streaming based H.265 - Hiba Khalid Abd al-azeez; Nasser N. Khamiss (Institute of Advanced Engineering and Science, 2020)
Using Ultra-High Definition (UHD) video streaming in real-time transmission over the internet is the main challenge of this paper. Due to the widely variation of the available Internet bandwidth makes the difficulties of video streaming with flexibility and efficiency. In this paper the UHD video is down sampled and encoded at different levels of 4K, FHD, 720p, 4CIF, CIF and QCIF. Experiments were done to find the optimal configuration of H265 features at each level that give the required PSNR, 36 dB, at assigned bitrate. A controller is incorporated with H265 encoder to achieve the adaptation of video streaming on the available bandwidth by choosing the proper level that is compatible with the channel bitrate results of keeping a good quality to the end user. The adaptation of video was realized by making the controller periodically reads the status of the buffer, such function helps the controller to select the proper level, 4K, FHD, 720p, 4CIF, CIF or QCIF to be streamed over the channel. At the decoder the reconstructed video for lower level is done by interpolation scaling up.